BREAST RECONSTRUCTION USING EXPANDER AND FAT GRAFTING AFTER MASTECTOMY ASSOCIATED TO RADIOTHERAPY - Flores, Bruno Bohrer; Piñeres, Maria del Rosario Sarmiento; Vieira, Roberto José da Silva; Chagas, Carlos Ricardo; Pinho, Gabriela Volkart (Mastology, 2017)
Breast surgery has evolved very rapidly in recent years. New oncoplastic techniques have emerged, which allowed the maintenance of a good approach in surgical treatment of breast cancer, reducing the physical and mental suffering of the patients for presenting better aesthetic results. This case report refers to a 45-year-old female patient who underwent mastectomy and radiotherapy eight years ago due to breast cancer, and had her breast reconstructed with the use of a submuscular expander associated to fat grafting. This study aimed to show a therapeutic option in breast reconstruction.